The macroeconomic impact of the energy and climate provisions of the US Inflation Reduction Act: Evidence for the EU - Salvador Barrios Cobos; Jonathan Pycroft; Andrzej Leszek Stasio; Daniel Stoehlker (European Commission, Joint Research Centre (JRC), 2023)
We assess the extent to which the 391bn of energy and climate tax provisions under the Inflation Reduction Act in the United States could lead to a potential reallocation of investment and production activities away from the European Union. The analysis is based on the JRC's CORTAX multi-country, general equilibrium model in order to provide estimates of the potential impact of the IRA on main macroeconomic aggregates for the EU as a whole and the US. Our results suggest that, if the US had adopted the subsidies scheme unilaterally, the IRA provisions would have boosted investment in this country at the expense of investment in the EU. However, taking into account available funding from various EU programmes that are planned under the current Multiannual Financial Framework and NextGenerationEU (e.g. from the Recovery and Resilience Facility), the simulation results suggest that EU green sectors would significantly increase their activity while the positive impact on the EU economy as a whole would be positive and noticeable.
Keywords: 330